2010
DOI: 10.1177/1534484310370312
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Personal Politics

Abstract: The ability to effectively navigate organizational politics to achieve one's goals has long been recognized as necessary for individuals to experience success within their organizations. Many studies have linked the effective use of political behaviors to increased individual performance. As such, many scholars within HRD and other disciplines have created practitioner techniques and models to guide individuals in their pursuit of personal success within an organization. Although these tools are useful, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…While many other studies have linked the effective use of political behaviors to improvement of individual performance (25), TUMS employees disagreed with use of political behavior to improve individual performance. However, Comer believed that political behavior may not only influence decision making but also reflect organizational objectives and individual interest and inclinations (26).…”
Section: Discussionmentioning
confidence: 99%
“…While many other studies have linked the effective use of political behaviors to improvement of individual performance (25), TUMS employees disagreed with use of political behavior to improve individual performance. However, Comer believed that political behavior may not only influence decision making but also reflect organizational objectives and individual interest and inclinations (26).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that employees of Tehran University of Medical Sciences believe that improvement of individual and organizational performance depends on non-political environments in their organizations. Although, other researchers reported that effective use of political behavior in organizations promotes organizational performance, affects logical decision-makings, and attaining organizational goals (Fritsch, 2010;Comer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These models and frameworks could also be developed by a skillful use of other models and literature. Fritsch (2010) developed "a cross-disciplinary framework for a theory of personal politics" (p. 226). After providing a background and purpose, Fritsch defines the term politics and explains how this framework could contribute to HRD.…”
Section: Suggest a Foundation For A New Theorymentioning
confidence: 99%